The challenges of COVID-19 for community pharmacists and opportunities for the future. (21st September 2020) - Hayden, John C.; Parkin, Rebecca
Abstract : Pharmacists, like psychiatrists, have modified their practices amidst COVID-19 in order to guarantee care and support to their patients. Designated an essential frontline service, community pharmacists are facing a spectrum of challenges to surmount to ensure patient care continues. These include assisting in the prevention of infection, managing supply chains, preventing stockpiling and provision of evidence-based medical information. However, disasters like COVID-19 disproportionately affect poor and vulnerable populations, and patients with mental health conditions may be among the hardest hit. Pharmacist-level, system-level and regulatory responses have sought to minimise this impact, although there is likely to be a lasting impression on the profession, both good and bad. This article reviews the pandemic-related challenges and responses by pharmacists, as well as forming recommendation for areas of professional support and role expansion, particularly in the case of mental health.